ARTIFICIAL INTELLIGENCE UTILIZATION BY TEACHERS IN ELEMENTARY SCHOOL TEACHING AND LEARNING PROCESS AT SCHOOL CLUSTER III, NORTH KUTA DISTRICT - Ni Luh Nita Sari (RADJA PUBLIKA, 2026)
This study was conducted in response to the continued dominance of teacher-centered instructional methods that limit media variation, teacher creativity, and student engagement. This study aims to identify the profile of teachers’ utilization of Artificial Intelligence (AI), its role in the teaching and learning process, its contribution to teachers’ competence and creativity, as well as the supporting and inhibiting factors influencing AI utilization. A quantitative approach using a survey method was employed. The population consisted of all elementary school teachers in School Cluster III, North Kuta District, with 58 teachers selected through purposive sampling. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed using descriptive statistics. The results indicate that the profile of AI utilization by teachers is categorized as high. The role of AI in teaching and learning is also high, particularly in lesson planning and implementation, while its utilization in learning evaluation remains moderate. AI contributes positively to teachers’ competence and creativity by fostering reflective and innovative teaching practices. Supporting factors are categorized as high, whereas inhibiting factors are moderate. Overall, teachers demonstrate good readiness to utilize AI, although continuous training is necessary to optimize its implementation.